Levantamento populacional de nematoides em soja no Rio Grande do Sul e estratégia genética, química e biológica para controle de nematoides de galha - Mazzetti, Valéria Cecília Ghissi (2017)
Phytonematodes constitute an important group of soybean pathogens, which if not properly managed, cause significant damage to the crop. The objectives of this study was to identify and quantify the species of nematodes present in the soybean crop among municipalities of Rio Grande do Sul and to evaluate the efficacy of genetic, chemical and biological methods for Meloidogyne javanica control. The frequency, incidence and population density of nematode species in soybean crop in different municipalities in the north of Rio Grande do Sul were determined through soil and root samples collection. Subsequently, the reaction of soybean cultivars to M. javanica and M. incognita was determined in greenhouse trials. Twenty-seven cultivars of soybean with the highest market representativeness in the northern region were cultivated. Moreover, the nematicidal action of chemical and biological products on the hatching, mobility, mortality and control of M. javanica was determined in vitro. The main soybean nematode species found in farms of the north of Rio Grande do Sul were M. javanica and M. incognita, Pratylenchus brachyurus and P. zeae, Heterodera glycines, Rotylenchulus reniformis and Helicotylenchus dhystera, with H. Dihystera being the most frequent in both samples and locations. For the test reaction of the cultivars, a difference between cultivars for root knot nematodes was verified. For M. javanica, 40.7% of the cultivars were considered susceptible, while 59.2% were considered resistant. For M. incognita, 81.5% of soybean cultivars were considered susceptible and 18.5% resistant. It is also considered that nematicides interfere in the hatching and mobility of nematodes, and that the products Fluopyram, Fluensulfone, Cadusafos and Abamectin are the most efficient for M. javanica control.